Inhibitory effect of ginsenoside Rg3 on cancer stemness and mesenchymal transition in breast cancer via regulation of myeloid-derived suppressor cells. - Joong-Hyun Song; Da-Young Eum; Soon-Yong Park; Yun-Ho Jin; Jae-Woong Shim; Shin-Ji Park; Min-Young Kim; Seong-Jun Park; Kyu Heo; Yoo-Jin Choi (PLoS ONE, 2020)
Ginsenoside Rg3 (Rg3) has been studied in several cancer models and is suggested to act through various pharmacological effects. We investigated the anticancer properties of Rg3 through myeloid-derived suppressor cell (MDSC) modulation in FM3A mouse mammary carcinoma cells. The effects of Rg3 on MDSCs and consequent changes in cancer stem-like cells (CSCs) and epithelial-mesenchymal transition (EMT) were evaluated by diverse methods. MDSCs promoted cancer by enhancing breast cancer stemness and promoting EMT. Rg3 at a dose without obvious cytotoxicity downregulated MDSCs and repressed MDSC-induced cancer stemness and EMT. Mechanistic investigations suggested that these inhibitory effects of Rg3 on MDSCs and corresponding cancer progression depend upon suppression of the STAT3-dependent pathway, tumor-derived cytokines, and the NOTCH signaling pathway. In a mouse model, MDSCs accelerated tumor progression, and Rg3 delayed tumor growth, which is consistent with the results of in vitro experiments. These results indicated that Rg3 could effectively inhibit the progression of breast cancer. The anticancer effect of Rg3 might be partially due to its downregulation of MDSCs and consequent repression of cancer stemness and EMT in breast cancer. Hence, we suggest the regulation of MDSCs through Rg3 treatment as an effective therapeutic strategy for breast cancer patients.